Imitation in Sixteenth-century Portuguese Eclogues: Diogo Bernardes, Camões, António Ferreira - Ferreira, Ana (2016)
The concept of imitation, as a creative process, allows for different ways of referring to a model text, as the author may prefer the resemblance to be more or less apparent. While it might be expected that Diogo Bernardes would follow his "mestre" António Ferreira, and stick very closely to the imitated text, in fact, like Luís de Camões, he favours imitation as Petrarch defined it, relying on similitudo. Both Bernardes and Camões aim clearly at emulation and producing an original poem, one that resembles Virgil and Sannazaro, and at the same time is entirely new.